A Journey of Growth of FDI (Foreign Direct Investment) in Indian Retailing - Kumar, Prashant; Kavita, - (International Journal of Social Sciences and Management, 2016)
Foreign Direct Investment (FDI) in retail has recently generated tremendous high spirits for a few and concern for others. It is supported that it will open floodgates for foreign retailers to speculate and can modification the retail landscape forever in India. FDI in retailing is much talked concerning subject by politician, media, trade specialist and industry experts. The Indian Retail market particularly the small Kirana store is not so well known by the actual means of FDI. The views given by politicians on the topic are terribly numerous and changes from party to party and person to person that has supplementary confusion in mind of those individuals. Retailing in Indiais the pillar of economy and accounts for about 22 percent of its GDP. The Indian retail sector is estimated to be US 500 billion and one of the top five retail markets in the world. India is the fastest growing retail markets in the world with 1.2 billion people.The Retail Business in India is presently at the point of inflection. As of 2008, speedy amendments with investments of US 25 billion were being planned by many Indian international firms within the next 5 years. The present study intends to explore the growth trends of FDI in Indian retail sector and also determine the SWOT (Strengths, weaknesses, opportunities and threats) analysis of Indian retail Industry. Int. J. Soc. Sci. Manage. Vol-3, issue-2: 129-134